Molecular Characterization of GABA-A Receptor Subunit Diversity within Major Peripheral Organs and Their Plasticity in Response to Early Life Psychosocial Stress - Everington, Ethan A.; Gibbard, Adina G.; Swinny, Jerome D.; Seifi, Mohsen (Frontiers in Molecular Neuroscience, 2018)
Gamma aminobutyric acid (GABA) subtype A receptors (GABAARs) are integral membrane ion channels composed of five individual proteins or subunits. Up to 19 different GABAAR subunits (α1-6, β1-3, γ1-3, δ, ε, θ, π and ρ1-3) have been identified, resulting in anatomically, physiologically and pharmacologically distinct multiple receptor subtypes, and therefore GABA-mediated inhibition, across the central nervous system (CNS). Additionally, GABAAR-modulating drugs are important tools in clinical medicine, although their use is limited by adverse effects. While significant advances have been made in terms of characterising the GABAAR system within the brain, relatively less is known about the molecular phenotypes within the peripheral nervous system (PNS) of major organ systems. This represents a potentially missed therapeutic opportunity in terms of utilising or repurposing clinically available GABAAR drugs, as well as promising research compounds discarded due to their poor CNS penetrance, for the treatment of peripheral disorders. In addition, a broader understanding of the peripheral GABAAR subtype repertoires will contribute to the design of therapies which minimise peripheral side-effects when treating CNS disorders. We have recently provided a high resolution molecular and function characterisation of the GABAARs within the enteric nervous system of the mouse colon. In this study, the aim was to determine the constituent GABAAR subunit expression profiles of the mouse bladder, heart, liver, kidney, lung and stomach, using RT-PCR and western blotting with brain as control. The data indicate that while some subunits are expressed widely across various organs (α3-5), others are restricted to individual organs (γ2, only stomach). Furthermore, we demonstrate complex organ-specific developmental expression plasticity of the transporters which determine the chloride gradient within cells, and therefore whether GABAAR activation has a depolarising or hyperpolarising effect. Finally, we demonstrate that prior exposure to early life psychosocial stress (ELS) induces significant changes in peripheral GABAAR subunit expression and chloride transporters, in an organ- and subunit-specific manner. Collectively, the data demonstrate the molecular diversity of the peripheral GABAAR system and how this changes dynamically in response to life experience. This provides a molecular platform for functional analyses of the GABA-GABAAR system in health, and in diseases affecting various peripheral